The Reflection of the Adoption of IFRS 17 “Insurance Contracts” on the Procedures for Auditing Insurance Contracts in the Iraqi Environment - Al-Mohammadi, Mohammed Falah; Al-Mashhdani, Bushra N. Abdullah (Journal of Economics and Administrative Sciences, 2021)
IFRS 17 aims to provide a unified basis for accounting for all types of insurance contracts, including reinsurance contracts, in a manner that benefits both investors and insurance companies and enhances the ability of the financial statements of insurance companies for comparison between companies listed in financial markets around the world. According to this standard, insurance contracts are accounted for on the basis of the Asset-Liability Approach and the use of fair values that the standard requires updating regularly in order to provide more useful information to the users of financial statements, as a result of the failure of reporting requirements for insurance contracts in the Iraqi environment to provide adequate and honestly representative information about the result of the activity and the financial position as a result of the failure of the requirements of the unified accounting system for banks and insurance companies with regard to providing appropriate bases for recognition, measurement, presentation and disclosure of insurance contracts compared to IFRS 17. Consequently, the insurance contracts audit program prepared by the Federal Board of supreme audit is insufficient and lacks the necessary procedures, also, this program includes audit procedures for insurance companies only and does not include companies that deal in contracts of an insurance nature, as well as the absence of an integrated program or guide approved by private auditing companies and offices in the Iraqi environment for the purpose of auditing these contracts, which requires a statement of the importance of adopting the International Financial Reporting Standard IFRS 17 and its reflection on the audit procedures that auditors must adopt when auditing insurance contracts. The two researchers relied on the opinions of a sample of academics and professionals specialized in this field by preparing a questionnaire that focused on the importance of adopting IFRS 17 and the reflection of adoption on the procedures for auditing these contracts in the Iraqi environment. The most prominent finding of the research is the need to adopt IFRS 17 because it provides clear and specific guidelines that help provide more useful information to users of financial statements in companies that deal in insurance contracts, as well as the impact of adopting this standard on the insurance contract audit procedures approved by the Federal Board of supreme audit and private auditing companies and offices in the Iraqi environment